A comparative study on the structural, optical and magnetic properties of Fe3O4 and Fe3O4@SiO2 core–shell microspheres along with an assessment of their potentiality as electrochemical double layer capacitors. Issue 16 (19th March 2015) - Majumder, S.; Dey, S.; Bagani, K.; Dey, S. K.; Banerjee, S.; Kumar, S.
Abstract : Study on magnetic and hyperfine properties of Fe3 O4 and Fe3 O4 @SiO2 microspheres. Both can be used as EDLC. Abstract : Herein, we report a comprehensive and comparative study on the crystal structure, and microstructural, optical, magnetic, hyperfine and electrochemical properties of Fe3 O4 microspheres (S1) of diameter ∼418 nm and Fe3 O4 @SiO2 core–shell microspheres (S2) of diameter ∼570 nm. Each asymmetric unit of the crystalline Fe3 O4 has one cation vacancy at the octahedral [B] site. At 300 K the saturation magnetization and coercivity of ferrimagnetically ordered S1 and S2 are 63.5, 38.5 emu g −1 and 200 and 120 Oe, respectively. We have shown that the synthesis procedure, morphology, surface properties, interparticle interaction manifesting the collective properties of the nanoparticle assembly and the average size of individual Fe3 O4 nanoparticles forming the spherical ensemble play a crucial role in determining the magnetic properties of Fe3 O4 and Fe3 O4 @SiO2 microspheres while the diameter of the microsphere does not have significant influence on magnetic properties of such a system. Further, the photoluminescence intensity of Fe3 O4 microspheres gets significantly enhanced upon SiO2 coating. A cyclic voltammetric study suggests that S1 can act as a good electrical double layer capacitor (EDLC) above a scan rate of 0.04 V s −1 while S2 exhibits excellent performance as EDLC in a scan range from 0.01 to 0.06 V s −1 . Thus, S2 is a potential candidate for fabrication of EDLCs.